2013
DOI: 10.1371/journal.pone.0064918
|View full text |Cite
|
Sign up to set email alerts
|

Pretherapeutic Plasma Pro- and Anti- Inflammatory Mediators Are Related to High Risk of Oral Mucositis in Pediatric Patients with Acute Leukemia: A Prospective Cohort Study

Abstract: ObjectiveThis prospective study evaluated clinical risk indicators as well as pro- and anti- inflammatory mediators at the time of malignancy diagnosis in relation to chemotherapy-related oral mucositis in pediatric population.MethodsPatients (n = 104) under 18 years of age with primary malignancies and undergoing chemotherapy were included. Potential risk indicators were analyzed using binary logistic regression with oral mucositis as the outcome. In a subgroup (n = 35), plasma samples at the time of malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 24 publications
4
38
2
Order By: Relevance
“…Other authors [25] have observed mucositis percentages higher than those found in this study. The results of research conducted in São Luis (Brazil) [17] were different than those of this study, as few cases of mucositis occurred during anticancer treatment for leukaemia. This finding was likely due to the small sample, which included only 12 individuals.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Other authors [25] have observed mucositis percentages higher than those found in this study. The results of research conducted in São Luis (Brazil) [17] were different than those of this study, as few cases of mucositis occurred during anticancer treatment for leukaemia. This finding was likely due to the small sample, which included only 12 individuals.…”
Section: Discussioncontrasting
confidence: 93%
“…Many national and international studies in the literature show a correlation between anticancer treatments, particularly chemotherapy and the occurrence of oral complications in infant-juvenile patients and adults [7, 10, 1726], and the magnitude of these side effects depends on a number of factors related to the treatment, tumour and patient [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the incidence of oral mucositis differs according to the type of cancer and treatment regimen, suggesting that it is more frequent in those with hematological malignancies compared with patients suffering solid tumors [10][11][12][13]. Based on the occurrence of oral mucositis is different in these groups of tumors [10], in the present study, the patients were divided into two groups-hematologic malignancies and solid tumors.…”
Section: Discussionmentioning
confidence: 78%
“…Neutropenia and lymphopenia are common findings among patients with hematologic malignancies and might also develop as an adverse effect of treatment [11,16]. According to one study, a reduction in neutrophils count can result in inefficient protection against damage to the oral mucosa and can impair epithelial cell proliferation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study reported that, at the time of diagnosis of acute leukemia, high prechemotherapy plasma levels of both pro- and anti-inflammatory cytokines and low levels of an antimicrobial protein pro-LL-37 were associated with the highest OM risk, suggesting that a proinflammatory state preceding high-dose chemotherapy may predispose to complications [196]. …”
Section: Discussion and Suggestions For Future Researchmentioning
confidence: 99%